A Comparison of the Effects of Beef, Chicken and Fish Protein on Satiety and Amino Acid Profiles in Lean Male Subjects - Uhe, Anthony M.; Collier, Greg R.; O’Dea, Kerin (The Journal of nutrition, 1992)
We compared postprandial satiety and plasma amino acid, insulin, and glucose concentrations in six lean male subjects after the ingestion of three types of protein (beef, chicken and fish). Satiety was greater after the fish meal (P < 0.01). The observed difference in satiety could be correlated with two of the putative satiety signals measured in this study: 1) serotoninergic activity, due to differences observed in the postprandial tryptophan to large neutral amino acid ratio; and 2) digestibility, reflected in the significantly (P < 0.05) longer time it took for the plasma amino acid concentrations to peak after the fish meal. Correlations between dietary and plasma amino acid concentrations were determined and good correlations (r = 0.90) were observed for essential amino acids other than lysine and tryptophan. There were no differences in insulin or glucose concentrations in subjects after consuming each of the three meals. Whether other differences that we observed, such as increased concentrations of taurine and methionine following the fish meal, had any effect on satiety or were of biological significance is not known.